Honoring the Legacy of David Loye - Teddie Potter; Heidi Bruce; Stephanie Gingerich; Renee Pardello; Quincey Tickner (Interdisciplinary Journal of Partnership Studies, 2022)
David Loye’s legacy shines through many aspects of the work undertaken at the Interdisciplinary Journal of Partnership Studies (IJPS) and the Center for Partnership Systems (CPS). This article is a collection of tributes by journal editorial board members and CPS staff members in the form of personal reflections and key insights into Loye’s developed theory of moral sensitivity and his poetic contributions.